If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 6) + (10x + -30) = 0 Reorder the terms: (6 + 6x) + (10x + -30) = 0 Remove parenthesis around (6 + 6x) 6 + 6x + (10x + -30) = 0 Reorder the terms: 6 + 6x + (-30 + 10x) = 0 Remove parenthesis around (-30 + 10x) 6 + 6x + -30 + 10x = 0 Reorder the terms: 6 + -30 + 6x + 10x = 0 Combine like terms: 6 + -30 = -24 -24 + 6x + 10x = 0 Combine like terms: 6x + 10x = 16x -24 + 16x = 0 Solving -24 + 16x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 16x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 16x = 0 + 24 16x = 0 + 24 Combine like terms: 0 + 24 = 24 16x = 24 Divide each side by '16'. x = 1.5 Simplifying x = 1.5
| 2x^2-6x=80 | | 7-(4n-8)=7-5n | | 5[x-4]=2[x-7] | | 9x+4+3+8=12 | | 7x^2+76x=8 | | 18c-4-2c+12= | | 54=x+5x | | 8u-6u=6 | | 5[x-3]=4[x+2] | | 11=4+v | | 12p+6=8p+30 | | 9x-30=2x+5 | | 47+11x=-30 | | (4x+3)=25 | | 179=6-u | | X-5.67=8.2 | | 12+x=3(3-2x) | | 47+11x=30 | | x(2x+1)=5x+1 | | 4[2-x]=5[x-2] | | -6u=4 | | 6(n-4)-(3-5n)=10n | | 5x=3-2y | | 8*x^3-6*x-1=0 | | 47+11=30 | | 3-1x=1 | | 3(8n-2)+8=(5+2n)-38+8n | | 3x+4+2x+1=6x-7 | | 10*x*100=50 | | 236=118-x | | 10*x=50 | | 11X-225=2X-9 |